2010
DOI: 10.1016/j.physletb.2010.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Probing leptonic CP phases in LFV processes

Abstract: We study a CP and T violating triple (spin) correlation in the muon to electron conversion in nuclei in the context of the seesaw mechanism. After concluding that the results are negative for all three seesaw types, we turn to the left-right symmetric theories as the original source of seesaw. We find that in general this correlation is of order one which offers a hope of observing CP violation in lepton flavor violating processes for a L-R scale below around 10-30 TeV. We discuss the conditions that could ren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…On the other hand, a 100 TeV pp collider provides an unprecedented opportunity to probe the RH gauge boson masses up to ∼ 30 − 35 TeV [5,52,55], as well as the entire Higgs sector of the LR model, as demonstrated in this paper. There are also low energy tests of the model in the domain of leptonic physics, such as the LFV processes of µ → eγ, µ → 3e and µ − e conversion in nuclei [12,48,55,[71][72][73][74][75][76][77][78][79][80][81], electric dipole moment of neutron [82][83][84] and electron [85,86], as well as the LNV process of 0νββ [12,77,78,80,81,[87][88][89][90][91][92][93][94][95][96][97][98] which are the focus of the intensity frontier. Thus, the TeV-scale LR models straddle both the energy as well as the intensity frontier, although our main focus here will be on the energy frontier aspects of the LR Higgs sector.…”
Section: Contentsmentioning
confidence: 99%
“…On the other hand, a 100 TeV pp collider provides an unprecedented opportunity to probe the RH gauge boson masses up to ∼ 30 − 35 TeV [5,52,55], as well as the entire Higgs sector of the LR model, as demonstrated in this paper. There are also low energy tests of the model in the domain of leptonic physics, such as the LFV processes of µ → eγ, µ → 3e and µ − e conversion in nuclei [12,48,55,[71][72][73][74][75][76][77][78][79][80][81], electric dipole moment of neutron [82][83][84] and electron [85,86], as well as the LNV process of 0νββ [12,77,78,80,81,[87][88][89][90][91][92][93][94][95][96][97][98] which are the focus of the intensity frontier. Thus, the TeV-scale LR models straddle both the energy as well as the intensity frontier, although our main focus here will be on the energy frontier aspects of the LR Higgs sector.…”
Section: Contentsmentioning
confidence: 99%
“…In this work we focus on quantities that test T violation in the absence of finalstate interactions and among these quantities are triple vector correlations made up of the momenta or spins of the participating particles [10]. In [11], it is suggested that triplet vector correlations can be used to probe CP violation in the µ → e conversion process. Here we present the first analytical computation for the correlation suggested in [11] for the µ → e conversion process and we extend their work in two ways: first, we compute the correlation for the µ → eγ decay and second we include the full set of effective operators that enter the µ → e conversion process.…”
Section: Jhep09(2015)131mentioning
confidence: 99%
“…In [11], it is suggested that triplet vector correlations can be used to probe CP violation in the µ → e conversion process. Here we present the first analytical computation for the correlation suggested in [11] for the µ → e conversion process and we extend their work in two ways: first, we compute the correlation for the µ → eγ decay and second we include the full set of effective operators that enter the µ → e conversion process.…”
Section: Jhep09(2015)131mentioning
confidence: 99%
See 2 more Smart Citations